PENGARUH KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN SUPERVISI TERHADAP KINERJA GURU DIMODERASI OLEH BUDAYA ORGANISASI (Studi Kasus Guru SD Di UPT Dindikbud Doro Kabupaten Pekalongan) (Students' Journal of Economic and Management, 2012)
Target of this research to test influence ability of headmaster managerial and supervision to Elementary schoolteacher performance in UPT Dindikbud Doro Kabupaten Pekalongan immoderacy by organizational culture. Pursuant to the mentioned hence this research take title “Pengaruh Kemampuan Manajerial Kepala Sekolah Dan Supervisi Terhadap Kinerja Guru Dimoderasi Oleh Budaya Organisasi (Studi Kasus Guru SD Di UPT Dindikbud Doro Kabupaten Pekalongan)”. In this research take Elementary schoolteacher population in UPT Dindikbud Doro Kabupaten Pekalongan amounting to 221 people. Intake of Sample with sampling random technique that is intake of sample at random counted 143 responder. Pursuant to result of research which have been done by hence can know by Ability of headmaster managerial do not have an effect on significant to performance learn SD in UPT Dindikbud Doro Kabupaten Pekalongan. Supervision do not have an effect on significant to performance learn SD in UPT Dindikbud Doro Kabupaten Pekalongan. Cultural of organization do not have an effect on significant to performance learn SD in UPT Dindikbud Doro Kabupaten Pekalongan. Cultural of influence moderating organization ability of headmaster managerial to performance learn SD in UPT Dindikbud Doro Kabupaten Pekalongan and organizational culture do not influence moderating supervise to performance learn SD in UPT Dindikbud Doro Kabupaten Pekalongan. Keyword : Ability of managerial headmaster, supervision, organizational culture and performance.